DETERMINAN PERILAKU PENCEGAHAN PENULARAN TUBERKULOSIS PADA PENDERITA TUBERCULOSIS - Kistimbar, Siti; Latumenasse, Rony; Fitri, Yenti; Lestaluhu, Kasman; Wahyurianto, Yasin (Ensiklopedia of Journal, 2024)
Abstract: Based on the results of the preliminary study conducted, it was found that 20% of patients with tuberculosis had good behavior and as many as 80% of patients had bad behavior in preventing tuberculosis transmission. This shows that one of the factors that can affect the high number of tuberculosis cases in the Wanasari Health Center working area is that there are still many patients who behave badly in preventing tuberculosis transmission. The purpose of the study was to determine the determinants of tuberculosis transmission prevention behavior in patients with tuberculosis. This research is a quantitative research with cross sectional study design. The research was conducted in the working area of Wanasari Health Center, Brebes Regency. The population as well as the sample used in this study were 62 patients with tuberculosis in the working area of Puskesmas Wanasari Brebes Regency. The sample collection technique used total sampling. Data analysis was done univariate and bivariate. The results showed that there was a relationship between family support (p value: 0.013) and Tb prevention behavior. It is recommended that the health center provide counseling to the patient's family so that they can support the patient in the form of informational support and to the patient It is recommended that the patient use a mask when communicating with other people both inside and outside the home.Keywords: Family Support, Prevention, Tuberculosis.